Chemical Constituents of Vigna luteola and Their Anti-inflammatory Bioactivity - Sio-Hong Lam (Molecules, 2019)
Seventy-three compounds were identified from the methanol extract of V. luteola, and among these, three new (1–3) were characterized by spectroscopic and mass spectrometric analyses. The isolated constituents were assessed for anti-inflammatory potential evaluation, and several purified principles exhibited significant superoxide anion and elastase inhibitory effects.